2014
DOI: 10.1088/0143-0807/35/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Students’ misconceptions about Newton's second law in outer space

Abstract: Students’ misconceptions about Newton's second law in frictionless outer space were investigated. The research was formed according to an epistemic game theoretical framework. The term ‘epistemic’ refers to students’ participation in problem-solving activities as a means of constructing new knowledge. The term ‘game’ refers to a coherent activity that consists of moves and rules. A set of questions in which students are asked to solve two similar Newton's second law problems, one of which is on the Earth and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…The findings were supported by the misconceptions in Newton's law in outer space (Comins, 2001;Temiz & Yavuz, 2014;Rachmawati & Susanto, 2017). Otherwise, the contra-contextual results that opposed the findings in this research were found through deeper analysis (Piburn, 1988;Supeno et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…The findings were supported by the misconceptions in Newton's law in outer space (Comins, 2001;Temiz & Yavuz, 2014;Rachmawati & Susanto, 2017). Otherwise, the contra-contextual results that opposed the findings in this research were found through deeper analysis (Piburn, 1988;Supeno et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…Tópicos Quantidade Artigos Experiências/ demonstrações 20 Vogt & Wargo (1992, 1995; Mohler (1997); Williams (1997); Rogers & Wargo (1998); Casaburri & Gardner (1999) Na sequência, foi realizada a leitura iniciando pelos artigos encontrados no portal CAPES, Scielo e os relacionados nas Tabelas 2 e 3. O artigo de Galili (1995) trata de preconcepções acerca do conceito leveza, Hershey (2005) propõe uma experiência para o estudo de tropismos usando um Clinostato, e Temiz & Yavuz (2014) trata acerca da Segunda Lei de Newton no espaço extraterrestre. Como já observado, Hershey (2005) usa o Clinostato, mas o objetivo é ensinar Biologia e não a Física envolvida.…”
Section: O Clinostatounclassified
“…(3) Quais autores têm o propósito de inserir os mesmos em sala de aula? Inserção em sala de aula é tratado pelos autores (Galili 1995;Vogt & Wargo 1995;Rogers et al 1997;Williams 1997;Casaburri & Gardner 1999;Sausen 1999;Saba et al 2000;Alshibli2 2002;da Silva 2002;NASA5 2002;NASA2 2003;Cappellari 2005;Reis & Garcia 2006;Knechtel 2008;Lima 2008;Ribeiro & Galera 2009;Passoni et al 2011;Matthews et al 2012;Rodrigues et al 2012;Dietlein et al 2013;Dou et al 2013;Dittrich 2014;Temiz & Yavuz 2014;Tenório et al 2014;Morais 2015;Pesquero 2015;Sousa 2015;Vasconcelos & Marranghello (2015); An et al 2016;Baliscei 2016;Borragini 2016;Secco & Sukara 2016;Borragini 2017;Moura 2017;da Silva 2018;Dutra & Souza 2019;Rodrigues 2019); isto é realizado em diversos níveis de ensino, desde Ensino Fundamental até formação continuada de professores. Nestes trabalhos tem experiências, sequências didáticas, problematização, interpretação de conceitos, dentre outros, focalizando a sala de aula.…”
Section: O Clinostatounclassified
“…Kavram yanılgıları ağırlıklı olarak fizik, kimya, biyoloji, astronomi gibi doğa bilimleri; davranış bilimleri ve eğitim bilimleri alanlarında ciddi anlamda araştırılan önemli bir konu olmuştur (Baysen ve Silman, 2012;Brault Foisy, Potvin, Riopel ve Masson, 2015;Brown, 2014;Demir, Uzoğlu ve Büyükkasap, 2012;Erman, 2016;Francek, 2013;Kara ve Yeşilyurt, 2008;King, 2010;Kolçak, Moğol ve Ünsal, 2014;Motulsky, 2014;Ormrod, 2008;Peterson ve diğerleri, 1986;Sadler ve Sonnert, 2016;Temiz ve Yavuz, 2014). Kütüphanecilik ve enformasyon bilimi alanında az da olsa kavram yanılgısı ile ilgili yapılan çalışmalar bulunmasına rağmen, BAS'ın herhangi bir aşaması içerisinde değerlendirilebilen çalışmaların çoğunluğu alan literatürü dışında yer almaktadır.…”
Section: Kütüphanecilik Ve Enformasyon Bilimi Alanında Kavram Yanılgıunclassified